2015
DOI: 10.3346/jkms.2015.30.10.1509
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Uric Acid Concentration and Acute Kidney Injury after Coronary Artery Bypass Surgery

Abstract: An elevated serum concentration of uric acid may be associated with an increased risk of acute kidney injury (AKI). The aim of this study was to investigate the impact of preoperative uric acid concentration on the risk of AKI after coronary artery bypass surgery (CABG). Perioperative data were evaluated from patients who underwent CABG. AKI was defined by the AKI Network criteria based on serum creatinine changes within the first 48 hr after CABG. Multivariate logistic regression was utilized to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
10
0
2
Order By: Relevance
“…The relationship between serum uric acid and mortality risk in different populations, such as CKD patients [28], hemodialysis patients [29], peritoneal dialysis patients [30, 31], and the general population [32], has been confirmed. High SUA has also been reported to be an independent predictor for AKI [33, 34]. In this study, we found that AKI patients with elevated serum uric acid concentrations had a higher in-hospital mortality risk.…”
Section: Discussionsupporting
confidence: 65%
“…The relationship between serum uric acid and mortality risk in different populations, such as CKD patients [28], hemodialysis patients [29], peritoneal dialysis patients [30, 31], and the general population [32], has been confirmed. High SUA has also been reported to be an independent predictor for AKI [33, 34]. In this study, we found that AKI patients with elevated serum uric acid concentrations had a higher in-hospital mortality risk.…”
Section: Discussionsupporting
confidence: 65%
“…34 Our results also conflict with a number of published studies on the association between uric acid level and the development of AKI or risk for death. 39 Higher uric acid levels have been reported to predict the risk for AKI in hospitalized patients [40][41][42] and after cardiac surgery, [16][17][18] with some reports of a J-shaped association showing higher risk at both very low and high uric acid levels. 43 In the Atherosclerosis Risk in Communities Study, higher uric acid levels predicted risk for a hospital stay with AKI during a mean follow-up of 12 years, although results from Mendelian randomization analyses did not support a causal association.…”
Section: Discussionmentioning
confidence: 99%
“…44 Prior retrospective studies in cardiac surgery have found increased risk for postoperative AKI in patients with higher preoperative uric acid levels. 16,17,43 However, these prior studies in cardiac surgery adjust for kidney function as a dichotomous variable (estimated GFR < 60 mL/min/ 1.73 m 2 ), whereas adjustment as a continuous variable may address confounding by kidney function more appropriately. A recent prospective study in 247 patients undergoing cardiac surgery demonstrated that patients with preoperative uric acid levels ≥ 373 μmol/L (≥ 6.3 mg/dL) were at greater than 5-fold increased risk for the development of postoperative AKI even after adjustment for preoperative Scr level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both urate and calcium phosphate crystals could induce oxidative stress and the expression of chemokine, and lead to the renal tubular epithelium and acute alterations in auto-regulation of renal blood flow which contribute to the decrease of renal perfusion and the subsequent injury of renal tubule [8,9,10,11]. Elevated serum level of uric acid has been reported as a novel marker for predicting AKI and mortality in several clinical settings, such as admission, percutaneous coronary intervention, and surgery, especially cardiovascular survey [12,13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%